Dinâmica da maturação nuclear e citoplasmática de oócitos bovinos cultivados in vitro em meio suplementado com fulerol - Rita de Cássia Ferreira Tameirão Palhares (2020)
The efficiency of in vitro maturation (IVM) of oocytes is closely related to biochemical competence, intrinsic to the development of the oocyte and subsequent fertilization. IVM medium is supplemented in order to test and improve the oocyte potential for in vitro embryo production (IVEP). This study aimed to evaluate, in vitro, the dynamics of nuclear and cytoplasmic maturation of bovine oocytes cultured in IVM medium supplemented with fullerol. Fullerol is a nanomolecule derived from fullerene polyhydroxylation, it is stable and formed exclusively by carbon atoms. It is being used in some biological areas due to its antioxidant activity at lower concentrations. This study aimed to evaluate whether fullerol is able to block the resumption of meiosis in bovine oocytes matured in vitro. Two MIV media were used: the control treatment (CT), TCM 199 bicarbonate medium; and treatment with TCM 199 bicarbonate medium supplemented with 50nM fullerol (MF50). The oocytes were matured for 24 hours in a incubator at 38.5ºC, 5% CO2 and 95% humidity. The evaluation of nuclear maturation of CT (n = 300) and MF50 (n = 270) was performed every 6 hours, for 36 hours, by staining the oocytes with Hoechst 33342 and identifying the following stages: germinal vesicle (GV), breakdown of the germinal vesicle (GVB), metaphase I (MI) and metaphase II (MII). At cytoplasmic maturation, oocytes from CT (n = 197) and MF50 (n = 159) were evaluated every 12 hours, for 36 hours, stained with Mitotracker Orange (Life® Technologies, Carlsbad, CA, USA), according to cytoplasmic distribution of mitochondria. During the experimentation, there was difficulty in stripping the oocytes exposed to 50nM fulerol, as an observational information. Descriptively, after 6 hours of incubation, a delay in the nuclear maturation of the oocytes of the MF50 group was observed. At 6 hours of maturation, oocytes of the CT (19%) were in MI, while the MF50 were in GV or GVB, which also occurred with 12 hours. At 18 hours, while 46.3% of oocytes were matured on CT (oocyte in stage MII), on MF50 the percentage was 20%. Within 24 hours of maturation, it was observed 43.9% and 63.8% of matured oocytes for MF50 and CT groups, respectively. At 30 and 36 hours, the pattern of maturation was stable, but degenerate oocytes were identified. Regarding cytoplasmic maturation, there was a delay of 36 hours of maturation (P<0.05) in the MF50 group (53.9%) compared to the control group (69.8% of mature gametes). In relation to cytoplasmic immature oocytes, they were 10.4% for CT and 31.7% for MF50 (P<0.05). It is concluded that the addition of 50nM fullerol to the in vitro maturation medium possibly interfered in the expansion mechanism of cumulus oophorus cells, as well as delayed meiotic progression and cytoplasmic maturation of oocytes.